A Chinese Tai Chi Model: An Integrative Model beyond the Dichotomy of Student-Centered Learning and Teacher-Centered (Asian Education Studies, 2016)
There are two types of educational approaches: one is student-centered learning and the other is teacher-centered learning. Each approach has its strengths and challenges. Hence debate arises as to which one is more appropriate and this makes some educators confused. In the background of globalization and internationalization of education, the influence of student-centered theory is very profound and far-reaching. Rethinking the student-centered or teacher centered education is important for the development of modern education. We argue that the ancient Chinese Tai Chi philosophy may be an alternative approach to mediate this controversy by helping people to understand the dynamic balance of teaching and learning. According to Tai Chi philosophy, student may be considered as yin, while teacher as yang. A Tai Chi model of education focuses on the dynamic interaction of the teacher and the student. Moreover, based on the vision of the Tai Chi philosophy, a number of classical western education theories may be brought to a new perspective. The combination of the traditional Chinese philosophies and related western educational theories might open another window for modern educational theories development. In short, through the perspective of Tai Chi, education is a combination of interactive factors and approaches rather than a dichotomy of teaching and learning, and it requires wisdom for dynamic complementary exploration rather than learning as static events in the class.